Recent population dynamics in the Oviedo region (1970-2011) - Obeso Muñiz, Ícaro (Geographicalia, 2018)
In the last four decades, the population dynamics in Asturias has been characterised by the concentration of population in its central area. By focusing on singular population entities – the closest data to settlement, this article analyses the spatial pattern of these dynamics and determines the phases in which these changes have occurred in the Oviedo region. The spatial distribution of this phenomenon shows that the entities that have experienced a significant growth of population are located in the surrounding area of Oviedo and in the margins of the communication axes. On the other hand, the entities that have suffered a sharp demographic decline are located in markedly rural areas and also those affected by the end of mining and industrial activity.